2014
DOI: 10.1039/c4cp01448k
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and structural study of Pt-modified Au vicinal surfaces: a model system for Pt–Au catalysts

Abstract: Two single crystalline surfaces of Au vicinal to the (111) plane were modified with Pt and studied using scanning tunneling microscopy (STM) and X-ray photoemission spectroscopy (XPS) in ultra-high vacuum environment. The vicinal surfaces studied are Au(332) and Au(887) and different Pt coverage (θPt) were deposited on each surface. From STM images we determine that Pt deposits on both surfaces as nanoislands with heights ranging from 1 ML to 3 ML depending on θPt. On both surfaces the early growth of Pt ad-is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…Figure 4 shows a sphere model of the Pt/Au(332) surface structure with different scenarios that may arise upon Pt deposition on Au(332) depending on the Pt surface loading. For instance, at very low coverage, the incoming Pt atoms can be exchanged with Au atoms both in the terrace and at the step edge, with the more favorable position being the step edge position due to the uncoordinated nature of these type of atoms, as we were able to corroborate with STM 16 . Thus, the displaced Au atoms begin to form 2D agglomerates where new Pt atoms can condense, forming nanoislands of mixed composition.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Figure 4 shows a sphere model of the Pt/Au(332) surface structure with different scenarios that may arise upon Pt deposition on Au(332) depending on the Pt surface loading. For instance, at very low coverage, the incoming Pt atoms can be exchanged with Au atoms both in the terrace and at the step edge, with the more favorable position being the step edge position due to the uncoordinated nature of these type of atoms, as we were able to corroborate with STM 16 . Thus, the displaced Au atoms begin to form 2D agglomerates where new Pt atoms can condense, forming nanoislands of mixed composition.…”
Section: Resultssupporting
confidence: 77%
“…The effect of adding Pt on Au(332) is a transition from monolayer (ML) to bilayer (BL) heights of the nanoislands, as demonstrated by us in a previous report using scanning tunnelling microscopy 16 . Thus, component 2 could be ascribed to the topmost atomic layer of bi-layered nanoislands, with the atomic layer beneath being responsible for component 1.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The above picture of the surface is consistent with prior studies of Pt deposition on Au substrates. At low coverage, Pt is known to form 2D islands on Au, 88 with Pt embedded in the surface and subsurface layer to form a bimetallic interface. [88][89][90]91,92 Scanning tunneling microscopy of Pt evaporated on Au (111) shows that Pt embeds in the surface layer at ϑ < 0.03, and forms alloyed islands above this coverage with the Pt concentration of the islands increasing to 50% by the point of island coalescence.…”
Section: Resultsmentioning
confidence: 99%
“…Previous structural investigations have shown that the steps may contain kinks depending on the crystal miscut. 24 On this surface, pulsed molecular beam (MB) experiments under well-defined single collision conditions are conducted to investigate the kinetics of the methanol oxidation under isothermal conditions. As gold single crystal surfaces cannot activate molecular oxygen under ultra-high vacuum conditions, pulses of atomic oxygen supplied by a thermal cracker were used to allow for the oxidation reactions.…”
Section: Introductionmentioning
confidence: 99%